Efeitos da alimentação e digestão na contratilidade miocárdica de pítons (Python molurus) - Cipriano, Rafael Corrêa (2013)
Despite all the knowledge about the excitation-contraction coupling (E-C) in mammals, there are still large gaps in the knowledge of the cardiac myocytes physiology in other vertebrates. Thus, the study of groups underexplored such as reptiles is very important. Python snakes are of great interest regarding to the studies of the postprandial metabolism because the physiological responses are exacerbated when digesting large preys. Studies with these snakes showed hypertrophy of the cardiac tissue 2 to 3 days after feeding, coinciding with the peak of the specific dynamic action (SDA), but the consequences of this remodeling in myocardial contractility have not been studied, which was the purpose of this work. Specimens of Python molurus of both sexes, provided by the Jacarezário of UNESP / Rio Claro were brought to the Laboratory of Comparative Biochemistry and Zoofisiologia, UFSCar, where they remained for at least 15 days for acclimatization (30 °C). The snakes were divided into two groups: 28 days (sacrificed 28 days after feeding) and 2 days (sacrificed 2 days after feeding, in the peak of the SDA). Each snake (n = 10) was fed (Wistar rats with a 30% weight of the snake) and the sacrifice (decapitation) occurred according to the experimental feeding regime. After sacrifice, the hearts were removed, weighed to calculate the relative ventricular mass (MVR) and ventricular strips were prepared to analyse the following parameters: peak force (Fc), times to peak force (TPT) and to 50% relaxation (THR), the effect of experimental time (40 min), elevation of the stimulation frequency and post-rest tension, being the latter two protocols performed in the presence and absence of ryanodine. Differences were considered significant at p <0.05 (Student's t test). When compared to group 28 days, animals of group 2 days showed a significant increase in MVR. The Fc values in the protocols of effect of time and increasing frequency of electrical stimulation were higher in group 2 days when compared to the group 28 days. The rates of contraction and relaxation were lower in group 2 days, and the derivatives of the maximum contraction and relaxation showed higher values for this group compared to the group 28 days, indicating greater efficiency in the processes of contraction and relaxation during E-C coupling. In the post-rest tension protocol, there was no significant difference in force developed before and after the pause in control preparations, but the ryanodine reduced Fc of the first contraction after the pause in both groups. The increasing frequency of stimulation in the presence of ryanodine abolished the difference between the values of all analyzed parameters presented by the two experimental groups. The increase in the MRV of group 2 days associated with a greater efficiency of Ca2+ transport in cardiac tissue was responsible for the increase in Fc, important for maintaining cardiac output and blood flow at the high metabolism during digestion. The RS appears to contribute significantly to the calcium dynamics during E-C coupling of P. molurus, but further studies are necessary to fully understand this process.